THE IMPACT OF DIGITAL WORK SYSTEMS AND INFORMATION SYSTEMS ON EMPLOYEE PERFORMANCE: Work Models in Society 5.0 Era - Caesario, Agus (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Since the pandemic occurred, the digital work model has begun to be implemented in many companies. This was done as a solution to overcoming work constraints due to Covid-19 and government regulations regarding restrictions on interactions. However, even though the pandemic status has been revoked, the digital work system is seen as more efficient in creating an effective work system and increasing employee performance. Based on this explanation, this research was conducted to describe employee performance in digital work models and information systems. To prove the research objectives, a quantitative-based survey method was used. Where the research data was obtained through distributing questionnaires, with a Likert scale as the quantification of respondents' answers. The number of samples used was 100 people, all of whom were Startup Indonesia employees, using the incidental sampling technique. The collected research data were analyzed using multiple regression methods. The results of the study show that there is an increase in employee performance with the existence of a digital and information system-based work system. Digital work systems help facilitate employee work, while information systems create communication and coordination effectiveness, so that work processes can be carried out more efficiently.